2021
DOI: 10.1007/s10286-021-00830-5
|View full text |Cite
|
Sign up to set email alerts
|

Leg pain in neuropathic postural tachycardia syndrome is associated with altered muscle membrane properties

Abstract: Purpose In neuropathic postural tachycardia syndrome, peripheral sympathetic dysfunction leads to excessive venous blood pooling during orthostasis. Up to 84% of patients report leg pain and weakness in the upright position. To explore possible pathophysiological processes underlying these symptoms, the present study examined muscle excitability depending on body position in patients with neuropathic postural tachycardia syndrome and healthy subjects. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The finding that MPO-AAV-CFS patients have higher levels of lower leg pain than PR3-AAV-CFS patients is also of interest. Lower leg pain has shown to be associated with sympathetic dysfunction particularly in patients with postural tachycardia syndrome (POTS) 34 - a common feature in ME/CFS. A recent paper also found that the most frequent pain complaint in AAV patients was leg pain.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that MPO-AAV-CFS patients have higher levels of lower leg pain than PR3-AAV-CFS patients is also of interest. Lower leg pain has shown to be associated with sympathetic dysfunction particularly in patients with postural tachycardia syndrome (POTS) 34 - a common feature in ME/CFS. A recent paper also found that the most frequent pain complaint in AAV patients was leg pain.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Patients with POTS experience symptoms of orthostatic intolerance in the upright position such as lightheadedness, dizziness, palpitations, tremulousness, generalized weakness and leg pain, blurred vision, dyspnea, nausea, headache and cognitive dysfunction. [3][4][5][6] Many patients with POTS additionally report non-orthostatic symptoms of autonomic origin such as fatigue, gastrointestinal complaints, sleep disturbances, restless legs symptoms and exercise intolerance. 7,8 The exact etiology of POTS is still unknown, although in recent years evidence has accumulated that in a subset of patients with POTS the pathogenesis of dysautonomia may be immune-mediated.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Autonomic Research , Rodriguez and colleagues [ 5 ] examined muscle membrane properties in a small group of women with neuropathic POTS and with matched healthy controls. The tests were done in the supine position, following head-up tilt, and after recovery using a within-participants design.…”
mentioning
confidence: 99%